Targeting pro-protein convertase subtilisin kexin-9 as a novel therapy of hypercholesterolemia (Medical Journal of Indonesia, 2017)
Reducing low density lipoprotein (LDL) cholesterol level is an established primary and secondary prevention strategy for coronary heart disease. However, not all patients are able to achieve their LDL targets as recommended by the guidelines. Over the last 10 years, high plasma LDL level is known to be associated with a higher level of pro-protein convertase subtilisin kexin-9 (PCSK-9). Loss-of-function mutations in the PCSK-9 gene is associated with lower plasma LDL level and cardiovascular risk. Since its discovery in 2003, PCSK-9 has triggered many researchers to design a PCSK-9 inhibitor to reduce LDL cholesterol through competitive inhibition of this molecule. Some phase III clinical trials have showed promising results of PCSK-9 inhibitor efficacy in lowering LDL level and improving clinical outcome. This article aims to discuss the role of PCSK-9 in LDL metabolism and the efficacy of PCSK-9 inhibitor in reducing plasma LDL level.